Teaching Career Choices of Economics Education Students - Setiaji, Khasan (Dinamika Pendidikan, 2015)
This research aims to know the influence of career teaching motivation, career self-efficacy and socioeconomic status toward students’ academic achievement through students’ interests of being teachers. The research was a quantitative approach. The population of this study was all students of Economics Education on the first semester in academic year of 2012/2013. Data were collected by using questionnaires and documentation,  then analysed by using path analysis. Findings show that teaching career motivation, career self-efficacy and socioeconomic status have positive and significant influence on students’ academic achievement through the interest of being teachers. Based on the results of this study, it can be suggested that the efforts to foster students’ interest for being teachers and academic achievement can be done by improving their career motivation, career self-efficacy, and parents’ support. Then, preparation process for being teachers should consider some aspects such as talent, psychological interests, motivation, and career self-efficacy. Moreover, institution should provide learning facilities for students who are from poor families and have difficulties for getting the higher studies.